2010
DOI: 10.1016/j.bcp.2010.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Rimonabant-induced apoptosis in leukemia cell lines: Activation of caspase-dependent and -independent pathways

Abstract: Rimonabant (SR141716), a cannabinoid CB1 receptor antagonist known for anti-obesity activity, has more recently been shown to inhibit tumor cell growth. Here we demonstrated the anti-tumor potential of SR141716 in leukemia-derived cell lines and its low toxicity in normal cells (PBMC). SR141716(1-20 M range of doses) reduced Jurkat and U937 cell number by activating death signals as well as affecting cell cycle progression. The most prominent response in U937 to SR141716 was a G 0 /G 1 block, while in Jurkat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
3
16
0
Order By: Relevance
“…The cell lines L428, L540, KM-H2 and Karpas 422 were treated with CB 1 antagonist AM251 and viability was assessed using MTT-assay. Gallotta and colleagues observed a decrease in viability of Jurkat cells with an IC 50 of around 12 µM using SR141716, a CB 1 -antagonist with an affinity to CB 1 similar to AM251 [34]. Therefore, we tested viability of lymphoma cells using CB 1 ligands at a maximum of 10 µM each.…”
Section: Resultsmentioning
confidence: 99%
“…The cell lines L428, L540, KM-H2 and Karpas 422 were treated with CB 1 antagonist AM251 and viability was assessed using MTT-assay. Gallotta and colleagues observed a decrease in viability of Jurkat cells with an IC 50 of around 12 µM using SR141716, a CB 1 -antagonist with an affinity to CB 1 similar to AM251 [34]. Therefore, we tested viability of lymphoma cells using CB 1 ligands at a maximum of 10 µM each.…”
Section: Resultsmentioning
confidence: 99%
“…Whole lysates for immunoblotting analysis were prepared according to standard protocols. Cytosolic protein extracts for determining cytochrome c were prepared as described previously (16). Briefly, cells were gently lysed for 2 min in ice‐cold lysis buffer containing 0.05% digitonin.…”
Section: Methodsmentioning
confidence: 99%
“…The appetite suppressants reductil and rimonabant were prescribed for obesity, often in conjunction with DM, but have since been pulled from the market due to high risks for stroke and psychosis, respectively. In in vitro studies, rimonabant has been shown to have some anti-tumor activity [133], but is not safe for use in humans. Development of similar drugs is currently being explored [133].…”
Section: Obesitymentioning
confidence: 99%
“…In in vitro studies, rimonabant has been shown to have some anti-tumor activity [133], but is not safe for use in humans. Development of similar drugs is currently being explored [133]. Orlistat is a fatty acid synthase inhibitor with FDA approval for weight loss and has been shown to have some anti-tumoral effects in animal models of colorectal cancer [134], but there have been no epidemiological studies examining the effects of orlistat on cancer risk in patients with DM.…”
Section: Obesitymentioning
confidence: 99%